Understanding the measurement of women’s autonomy: Illustrations from Bangladesh and Ghana - Seymour, Gregory; Peterman, Amber (International Food Policy Research Institute, 2017)
The past decade has seen increased attention to measuring women’s empowerment and autonomy, motivated by the goal of identifying promising programs and policies for reducing gender inequalities. One of the most common quantitative indicators of women’s empowerment is the self-reported ability to participate in household decision making over important matters. Despite the widespread use of such indicators in the literature, uncertainty exists over how to construct valid indicators of empowerment based on questions about decision making. In particular, it is unclear how indicative joint decision making is of individual decision-making power and to what extent joint decision making reflects a consistent understanding of decision-making power within households. We utilize data from women and men in Bangladesh and Ghana to investigate whether respondents who report sole decision making in a particular domain tend to experience stronger or weaker feelings of autonomous motivation—measured using a Relative Autonomy Index—than those who report joint decision making. We find systematic differences between men and women in the association between feelings of autonomous motivation and decisionmaking outcomes. In addition, results vary by the domain of decision making and by whether or not there is a shared understanding of decision-making power within households. These findings suggest that in order to accurately measure empowerment, further innovation in the specificity as well as the sensitivity of indicators is needed.